Innovations in Managerial Accounting: A Review of Recent Developments - Yaya Sonjaya; Septyana Prasetianingrum; Muhammad Ridwansyah Pasolo (Advances in Management & Financial Reporting, 2025)
Purpose: This study aims to explore recent developments in managerial accounting, focusing on the integration of advanced technologies such as Big Data, Artificial Intelligence (AI), and Blockchain, and their implications for enhancing strategic decision-making and operational efficiency. Research Method: The research employs a qualitative design, utilizing semi-structured interviews, focus group discussions, and document analysis to gather insights from managerial accountants and financial analysts. Data were analyzed using thematic analysis to identify key themes and patterns. Results and Discussion: The study reveals that integrating these technologies has revolutionized accounting practices by enabling more accurate forecasting, improving efficiency through automation, and enhancing transparency in financial reporting. Despite the benefits, significant challenges, such as the need for new skills and ethical considerations related to data privacy and security, were identified. The findings support the hypothesis that technological advancements enhance decision-making and operational efficiency, aligning with theories of data-driven decision-making and technological substitution. Implications: The study highlights the evolving strategic role of managerial accountants and underscores the importance of continuous learning and professional development to leverage these innovations effectively. Practical implications include the need for robust data governance frameworks and the strategic use of predictive analytics to improve risk management and business performance. This research contributes to both academic knowledge and practical applications, offering a comprehensive understanding of how technological advancements are shaping managerial accounting.